The Movement Disorder Society Criteria for the Diagnosis of Multiple System Atrophy. Issue 6 (21st April 2022) - Wenning, Gregor K.; Stankovic, Iva; Vignatelli, Luca; Fanciulli, Alessandra; Calandra‐Buonaura, Giovanna; Seppi, Klaus; Palma, Jose‐Alberto; Meissner, Wassilios G.; Krismer, Florian; Berg, Daniela; Cortelli, Pietro; Freeman, Roy; et al.
ABSTRACT: Background: The second consensus criteria for the diagnosis of multiple system atrophy (MSA) are widely recognized as the reference standard for clinical research, but lack sensitivity to diagnose the disease at early stages. Objective: To develop novel Movement Disorder Society (MDS) criteria for MSA diagnosis using an evidence‐based and consensus‐based methodology. Methods: We identified shortcomings of the second consensus criteria for MSA diagnosis and conducted a systematic literature review to answer predefined questions on clinical presentation and diagnostic tools relevant for MSA diagnosis. The criteria were developed and later optimized using two Delphi rounds within the MSA Criteria Revision Task Force, a survey for MDS membership, and a virtual Consensus Conference. Results: The criteria for neuropathologically established MSA remain unchanged. For a clinical MSA diagnosis a new category of clinically established MSA is introduced, aiming for maximum specificity with acceptable sensitivity. A category of clinically probable MSA is defined to enhance sensitivity while maintaining specificity. A research category of possible prodromal MSA is designed to capture patients in the earliest stages when symptoms and signs are present, but do not meet the threshold for clinically established or clinically probable MSA. Brain magnetic resonance imaging markers suggestive of MSA are required for the diagnosis of clinically established MSA. The number of research biomarkers that support all clinical diagnostic categories will likely grow. Conclusions: This set of MDS MSA diagnostic criteria aims at improving the diagnostic accuracy, particularly in early disease stages. It requires validation in a prospective clinical and a clinicopathological study. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : MDS Criteria for the Diagnosis of Multiple System Atrophy